THE MODERATING ROLE OF INFORMATION TECHNOLOGY IN THE RELATIONSHIP BETWEEN WORK MOTIVATION, LEADERSHIP STYLE, AND LECTURER WORK PRODUCTIVITY IN ISLAMIC HIGHER EDUCATION - Ahmad Yani; Suharno Pawirosumarto; Muhammad Ridwan (Adisam Publisher, 2025)
This study examines the impact of leadership style, work motivation, and information technology on lecturer productivity in Islamic Higher Education Institutions (IHEIs) in Jambi Province, Indonesia. Using a quantitative research design, data were collected from 237 lecturers through a structured questionnaire, employing proportional stratified random sampling. The study found that leadership style, work motivation, and information technology have a positive and significant effect on lecturer productivity. Additionally, information technology was found to significantly moderate the relationships between work motivation and lecturer productivity, as well as between leadership style and lecturer productivity. The findings highlight the importance of transformational leadership, a motivated workforce, and robust IT infrastructure in enhancing academic performance in IHEIs. The study contributes to the literature by demonstrating how these factors interact to foster lecturer productivity and provides practical recommendations for improving academic excellence in higher education institutions.